2007
DOI: 10.1614/wt-05-168.1
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of Fomesafen in New York State Soils and Potential to Cause Carryover Injury to Sweet Corn

Abstract: The manufacturer's recommended rate for fomesafen in snap beans, dry beans, and soybeans may cause carryover injury in sweet corn. A field experiment, a survey, and multiple greenhouse experiments were conducted to (1) estimate the fomesafen residue concentrations in the soil that might result from use of lower than registered rates, (2) estimate fomesafen residue concentrations in growers' fields and evaluate grower practices for their effects on carryover potential, and (3) investigate the effects of soil ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 9 publications
1
30
0
1
Order By: Relevance
“…No entanto, sua sorção encontra-se estritamente relacionada com o pH do solo (Guo et al, 2003). Apesar de o fomesafen apresentar meia-vida de 66 dias, chegando a 100 dias em solos da região dos cerrados (Cobucci et al, 1998;Rauch et al, 2007), Artuzi & Contieiro (2006) não constataram efeitos negativos dele sobre o milho cultivado em sucessão à soja, após 90 dias após da aplicação deste herbicida. Embora a sucessão de culturas seja uma realidade no Brasil, pouco tem sido feito a fim de avaliar o efeito residual de herbicidas utilizados na cultura da soja sobre culturas de sucessão, como o milheto.…”
Section: Introductionunclassified
“…No entanto, sua sorção encontra-se estritamente relacionada com o pH do solo (Guo et al, 2003). Apesar de o fomesafen apresentar meia-vida de 66 dias, chegando a 100 dias em solos da região dos cerrados (Cobucci et al, 1998;Rauch et al, 2007), Artuzi & Contieiro (2006) não constataram efeitos negativos dele sobre o milho cultivado em sucessão à soja, após 90 dias após da aplicação deste herbicida. Embora a sucessão de culturas seja uma realidade no Brasil, pouco tem sido feito a fim de avaliar o efeito residual de herbicidas utilizados na cultura da soja sobre culturas de sucessão, como o milheto.…”
Section: Introductionunclassified
“…Then, the seeds were germinated in dishes in a growth chamber for 24 hours (Figure 3). The recommended field application dose of fomesafen was 3.75 mg kg -1 and an average half-life value of fomesafen was 50 d which means that the concentration of fomesafen in soil was 0.96 mg kg -1 after it had been applied 100 d (Rauch et al 2007;Wu et al 2014). So, in this study, 1 mg kg -1 was chosen as the concentration of fomesafen in soil.…”
Section: Methodsmentioning
confidence: 99%
“…Fomesafen applied preemergence in soybean as a selective herbicide with both root and shoot activity (Peachey et al 2012). But, it has been reported that recommended dosage of fomesafen in soybeans may cause carryover injury to corn and the injury was varied significantly by plant variety and soil conditions (Rauch et al 2007;Cieslik et al 2014). When sweet corn was sown in high pH and low organic matter soils, injury of fomesafen was more serious compared with other soil types.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, fomesafen degradation under anaerobic conditions was less than 3 weeks [5]. Rauch et al [31] reported fomesafen field DT 50 varied between 28 and 66 days. Fomesafen has been the focus of several research studies to determine its potential preemergence soil residual activity in vegetables, with testing in tomato for control of American black nightshade (Solanum americanum Miller) [32], cucurbits for Amaranthus spp.…”
Section: Fomesafenmentioning
confidence: 99%